Evaluating the Performance of Evacuation Routes in an Academic Facility Using Pathfinder Simulation and Regulatory - Aulia Herlina Putri; Noor Cholis Idham; Rania Ababssi (Journal of Architectural Design and Urbanism, 2025)
Effective evacuation routes are crucial in educational buildings, particularly in earthquake-prone regions, to ensure the safety of occupants during emergencies. One of the most significant issues identified in such contexts is the potential for bottlenecks during evacuation. These bottlenecks often result from confusion caused by unclear signage, poor distribution of exits, and high occupant density during peak academic hours. This study evaluated the effectiveness of evacuation routes in the Faculty of Islamic Studies (FIAI) of the Universitas Islam Indonesia (UII), Sleman, through an evaluative approach that combines direct field observation and agent-based evacuation simulation using Pathfinder software. Observations were conducted to assess corridor widths, signage placement, and physical obstructions, while the simulation examined pedestrian movement, evacuation times, and congestion points under high-density scenarios. The evaluation was also benchmarked against the Indonesian National Standard (SNI 03-1746-2000) and NFPA 101: Life Safety Code for evacuation planning as part of the methodological framework. The findings indicate that only the building’s structural components comply with the expected standards, while several supporting facilities—such as signage visibility, exit distribution, and circulation flow—require significant improvements. Enhancing these aspects is essential to improve overall evacuation performance and ensure safety in academic environments.